Regional modelling of extreme sea levels induced by hurricanes - A. A. Chaigneau; M. Menéndez; M. Ramírez-Pérez; A. Toimil (Natural Hazards and Earth System Sciences)
Coastal zones are increasingly threatened by extreme sea level events, with storm surges being among the most hazardous components, especially in regions prone to tropical cyclones. This study aims to explore the factors influencing the performance of numerical models in simulating storm surges in the tropical Atlantic region. The maxima, durations, and time evolutions of extreme storm surge events are evaluated for four historical hurricanes against tide gauge records. The Advanced Circulation (ADCIRC) and Nucleus for European Modelling of the Ocean (NEMO) ocean models are compared using similar configurations in terms of domain, bathymetry, and spatial resolution. These models are then used to perform sensitivity experiments on oceanic and atmospheric forcings, physical parameterizations of wind stress, and baroclinic/barotropic modes. NEMO and ADCIRC demonstrate similar abilities in simulating storm surges induced by hurricanes. Storm surges simulated with ERA5 atmospheric reanalysis forcing are generally more accurate than those simulated with parametric wind models for the simulated hurricanes. The inclusion of baroclinic processes improves storm surge amplitudes at some coastal locations, such as along the southeastern Florida peninsula (USA). However, experiments exploring different implementations of wind stress and interactions among storm surges, tides, and mean sea level have shown minimal impacts on hurricane-induced storm surges.